The Role of BRIspot Application in Improving Performance in Achieving Credit Targets with Process Speed as a Mediator at BRI Mojokerto - Wiranto, Triadi; Alimudin, Arasy (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
This study aims to examine the role of the BRISpot application in improving the performance of achieving credit targets at the BRI Mojokerto Branch, with process speed as a mediator. This research examines the influence of debtor data accuracy, ease of use of BRISpot, and BRISpot accessibility on the speed of the credit disbursement process and the performance of achieving credit targets. The analysis method uses descriptive and inferential statistics, as well as Structural Equation Modeling - Partial Least Squares (SEM-PLS) to examine the relationships between variables. The hypothesis testing results show that the speed of the credit disbursement process through BRISpot has a significant effect on the performance of achieving credit targets. Debtor data accuracy and BRISpot accessibility also have a significant effect on the speed of the process and the performance of achieving credit targets, while the ease of use of BRISpot only significantly affects the speed of the process. Based on these findings, it is recommended that companies improve debtor data accuracy, enhance the ease of use and accessibility of BRISpot, and pay attention to the speed of the credit disbursement process to improve the performance of achieving credit targets. Subsequent research could consider additional variables and delve into the factors influencing the ease of use of the BRISpot application and its impact on customer satisfaction and overall banking performance.